Energy matrices and enviroeconomical perspective of solar decontamination system. (2021) - Singh, Ashok Kumar; Srivastava, B.K.; Shankar, Vijay; Prasad, Rajendra; Yadav, R.K.; Shukla, Anoop Kumar; Nandan, Gopal; Kumar, P.
Highlights: Passive solar stills have been analyzed for EPF, EPT, LCCE and enviro-economic analysis. The combination is eco friendly as have good mitigation in CO2, SO2, NO emissions. System is enviro-economic with good amount of carbon credit earned. Still's EPT is quit less with appreciable LCCE. Abstract: The present era is living with very fast growing pace despite having the usual kind of natural resources available that are always we have in a limited amount with expansible and irreversible in nature. It has to be bothered about saving and sustaining our natural resources for better future along with the development of self sustainable, economic and environment friendly technology such as solar decontamination systems. And, current situation with water stress or even costlier potable water availability motivates us to work with such systems that have easy technology, self sustainable, and eco friendly establishment serving the society. This work shows a comparative performance analysis between single and double solar stills with four combinations as with circular and square fin, jute and black cotton wick for energy matrix and enviroeconomic considerations. Still with square fins found better and having less embodied energy (379.62 kWh) comparative to others. It has yield up to 4.55 l/m 2 /day with 36.6 tons CO2 lessening for thirty years of the overall systems performing life. Equivalent minatory value for the CO2 lessening scored by the proposed system is noticed as 365.63. Further, still have least time recovery for the equivalent energy payout and superior adaptation efficiency of the system through its working of life cycle i.e. 0.48 years, and 0.44 correspondingly.